CHROMATIC NUMBER TO THE TRANSFORMATION (G—) OF K(1,n) AND K(m,n) - John, B. Stephen (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
Let Â be an undirected simple graph. The transformation graph Â ofG is a simple graph with vertex set Â in which adjacency is defined as follows: (a) two elements in Â are adjacent if and only if they are non-adjacent in Â (b) two elements in Â are adjacent if and only if they are non-adjacent in Â and (c) an element ofÂ Â and an element ofÂ Â are adjacent if and only if they are non-incident in .In this paper, we determine the chromatic number of Transformation graph Â for Star and Complete Bipartite graph. Â Keywords: Star Graph, Complete Bipartite Graph, Chromatic Number, Transformation Graph